Redescription of the Leaf Miner on Ficus spp., Leiopleura melichari (Obenberger, 1922) (Buprestidae, Coleoptera) - Solís-Blanco, Ángel (2016)
Arboriculture is an essential component of urban landscapes and for the welfare of their inhabitants. Several Ficus species have been planted in San Jose (Costa Rica);of these, Ficus costaricana (Liebm.), F. citrifolia Mill.and F. jimenezii Standl. present foliage mining damage produced by Leiopleura melichari (Obenberger, 1922). This study presents the redescription of this species and the damage characterizations. Larvae produce extensive irregularly-shaped mines up to 65 mm at the most extensive parts; adults chew the upper plane of the leaf causing tissue necrosis. Oviposition takes place in groups (4.36 ± 1.64 eggs per group), with eggs measuring 0.88 ± 0.14 mm in diameter. Larvae are white, semi-translucent and can measure up to 12.09 + 0.74 mm long in their last instar. Adult bodies are oval and compact, lentiform, with convex upper and lower sides and blue-green and copper-red metallic coloration, measuring 3.7 ± 0.2 mm long and 2.5 ± 0.2 mm wide.